Comparison of Experiment and Simulation of the triple GEM-Based Fast Neutron Detector**Supported by the National Natural Science Foundation of China under Grant Nos 11135002, 11305232 and 11175076, and the Foundation of China Spallation Neutron Source: Study and Development of the High-performance and Low-angle Detector. (March 2015) - Wang, Xiao-Dong; Zhang, Jun-Wei; Hu, Bi-Tao; Yang, He-Run; Duan, Li-Min; Lu, Chen-Gui; Hu, Rong-Jiang; Zhang, Chun-Hui; Zhou, Jian-Rong; Yang, Lei; An, Lv-Xing; Luo, Wen
<x content-type="archive" xml:space="preserve">Abstract</x> A detector for fast neutrons based on a 10 × 10 cm2 triple gas electron multiplier (GEM) device is developed and tested. A neutron converter, which is a high density polyethylene (HDPE) layer, is combined with the triple GEM detector cathode and placed inside the detector, in the path of the incident neutrons. The detector is tested by obtaining the energy deposition spectrum with an Am Be neutron source in the Institute of Modern Physics (IMP) at Lanzhou. In the present work we report the results of the tests and compare them with those of simulations. The transport of fast neutrons and their interactions with the different materials in the detector are simulated with the GEANT4 code, to understand the experimental results. The detector displays a clear response to the incident fast neutrons. However, an unexpected disagreement in the energy dependence of the response between the simulated and measured spectra is observed. The neutron sources used in our simulation include deuterium-tritium (DT, 14 MeV), deuterium-deuterium (DD, 2.45 MeV), and Am Be sources. The simulation results also show that among the secondary particles generated by the incident neutron, the main contributions to the total energy deposition are from recoil protons induced in hydrogen-rich HDPE or Kapton (GEM material), and activation photons induced by neutron interaction with Ar atoms. Their contributions account for 90% of the total energy deposition. In addition, the dependence of neutron deposited energy spectrum on the composition of the gas mixture is presented.